Effect of PAN Oxidation on the Electrochemical Lithium Insertion/Deinsertion Behavior of Resultant Carbons - Aleksandra Piotrowska; Krzysztof Kierzek; Jacek Machnikowski (Journal of Chemistry)
The effect of polyacrylonitrile (PAN) oxidation on the properties and electrochemical lithium insertion/deinsertion behavior of carbons produced in the temperature range of 1000–1150°C has been assessed. Air-treatment at 220 and 240°C modifies essentially the carbonization behavior of polymer leading to materials with developed microporosity and enhanced oxygen content in contrast to practically nonporous pristine PAN-based carbon. The extent of the modification increases with the oxidation depth and decreases with HTT. Galvanostatic charge/discharge reveals typical hard carbons characteristics of all the materials. PAN-based carbon heat-treated at 1050°C represents most promising anodic performance. It gives reversible capacity (Crev) near 420 mAh g−1 with a reasonable coulombic efficiency during cycling of ~99% and a moderate low voltage capacity of 100 mAh g−1. Extensive oxidation enhances overall 1st discharge cycle capacity to 870 mAh g−1 and Crev to 560 mAh g−1; however, large irreversible capacity (Cirr) and poor cycleability are serious drawbacks of all carbons from oxidized PAN. Pyrolytic carbon coating using methane CVD at 830°C is effective in suppressing Cirr by about 30% but the cycleability remains nonacceptable.